Pengaruh Teknik Relaksasi Religius Terhadap Pemenuhan Kebutuhan Tidur Pada Lanjut Usia Di Panti Werdha Mojopahit Mojokerto - Agnes Cahyono (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2013)
Lack of sleep needs of the elderly is caused by extrinsic factors, for example, a crowded environment and intrinsic factor, which is organic and psychogenic. In organic like pain, itching and certain diseases could create anxiety. In psychogenic, like depression, anxiety and irritability. The purpose of this research is to analyze the influence of religious relaxation techniques to fulfill the needs of sleep of the elderly in Elderly Institution Mojopahit Mojokerto. Research design is the one group pre test and post test design. The independent variable is religious relaxation techniques and the dependent variable is the needs of sleep of the elderly. Population is all elderly which is living in elderly institution Mojopahit Mojokerto for some 50 seniors then it’s obtained some of the elderly who meet inclusion criteria as many as 32 people with a purposive sampling technique. Data is collected using the interview sheet on June, 4-26th, 2011. Data analysis is performed using Mc Nemar test Test. Before the implementation of religious relaxation techniques, mostly can’t meet their sleep needs as many as 20 respondents (62.5%) and after the implementation of religious relaxation techniques, most of them could meet their sleep needs as many as 20 respondents (62.5%). The result shows p (0.039) <α (0.05), means H0 is rejected and H1 is accepted. So there is the influence of religious relaxation techniques to fulfill the needs of sleep of the elderly in Elderly Institution Mojopahit Mojokerto. Fulfillment of sleep because of this relaxation response elicits feelings of calm and security and also relaxed body, make it easier to fall asleep and the quantity is met more than 6 hours. Changes toward the positive outweigh the negative direction. Local health workers are expected to direct more of the elderly to frequently apply religious relaxation techniques, so it can meet the need of rest sleep.